Analisis Kebutuhan Diklat (AKD) bagi Aparatur di Lingkungan Pemerintah Provinsi Riau - Kiswanto; Zainuri; Gevisioner; Heryudarini Harahap (Nakhoda: Jurnal Ilmu Pemerintahan, 2017)
The need to improve the competence of human resources needs to get serious attention from the local government. The human resources is a resources or operates other resources available within the organization. Alternative programs commonly used by an organization to improve the capability or competence or human resources is education and training (Diklat). The high demands of increasing the competence of apparatus in every SKPD in the Province Government of Riau bring the consequences to the many need education and training. Where, all the needs of the competences of development that match with the specifications and needs of the job in the field is certainly difficult to fulfill everything. This is due to various limitations, including a) Limited funds for education and training, b) Limited facilities and infrastructure of training institutions, and c) Limited manpower / human resources. Paying attention to Mid-Term Plan Develompent (RPJM) of Riau Province 2014-2019 (Bappeda of Riau Province, 2014), it can be put forward the priority agenda in fulfilling the needs of competence development for the apparaturs in the environment of the provincial government.